Johann Wolfgang von Goethe - Bloom, Harold; Loos, Pamela (Philadelphia : Chelsea House Publishers, 2003)
Presents fourteen critical essays on the writings of eighteenth-century German author Johann Wolfgang von Goethe, and includes a chronology of his life, a bibliography, and an introduction by Harold Bloom.
Includes bibliographical references (p. 265-268) and index.
Young Adult.
Young Adult
Keywords: Goethe, Johann Wolfgang von, -- 1749-1832 -- Criticism and interpretation; Goethe, Johann Wolfgang von, -- 1749-1832 -- Criticism; German literature -- History and criticism; German literature -- History and criticism